Perceptual Analysis of L2 Phonic Competence - Lengyelfalusy, Tomas; Kralova, Zdena (Communications - Scientific letters of the University of Zilina, 2010)
The research is focused on the quality of English pronunciation of Slovak native speakers reflected in the score of perceptual evaluation by English native speakers. The primary objective is to detect the improvement of English phonic competence after the metaphonetic input focused on the contrastive analysis of the Slovak and English segmental systems.